Inovasi Pembelajaran Model Inkuiri Terbimbing Menggunakan Padlet, Chat GBT, dan Media Sosial untuk Menjembatani ‘Ways to Know’ Siswa - Nabilla Hadistia; Solikhah Isti Fadilah; Riandi Riandi (Universitas Nusantara PGRI Kediri, 2024)
The independent curriculum demands learning outcomes that emphasize problem solving and science process skills. Guided inquiry learning is the right choice to use as a learning model where teachers and students both play a role. The literature review carried out aims to examine how innovation can be carried out in the implementation of inquiry learning in Indonesia on biological material. The method used in this research is rapid literature review (RLR). The results of the study gave rise to several innovations in almost every inquiry syntax. Technological innovations that can be implemented include: the use of practical formulas in presenting problems; the use of the Padlet application in the step of asking questions; the use of microscopes, Chat GBT, and cameras in answering questions; the use of the Padlet application in collecting the results of scientific investigations; and the use of social media in communicating the results of investigations. It is hoped that the innovation obtained can give rise to students 'ways to know’, which will be answered through investigation. Inquiry will invite students to be able to build and explore knowledge as scientists do.